2014
DOI: 10.6090/jarq.48.471
|View full text |Cite
|
Sign up to set email alerts
|

Winter Wheat Growth Monitoring Using Multi-temporal TerraSAR-X Dual-polarimetric Data

Abstract: This paper describes a method for monitoring winter wheat growth using multi-temporal TerraSAR-X dual-polarimetric data. Six TerraSAR-X HH/VV images were collected in Hokkaido, and the temporal responses to the winter wheat fields were analyzed. The height, moisture content and dry matter of the crops were measured at nearly the same time as TerraSAR-X data was acquired, and the relationships between these parameters and SAR data, including sigma naught and coherence, were studied. Quadratic relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In contrast, for Sentinel-1 C-SAR data, all J-M distance values were <1.0. Vertical polarized microwaves have a less penetration than horizontal polarized waves over mature wheat fields [14], and their intensity is decreased via absorption by the vertical structure of dense, narrow stems [25,63]. The main scattering pattern was surface scattering and the intensity was low in August, with the result that the differences in sigma naught were small.…”
Section: Separability Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for Sentinel-1 C-SAR data, all J-M distance values were <1.0. Vertical polarized microwaves have a less penetration than horizontal polarized waves over mature wheat fields [14], and their intensity is decreased via absorption by the vertical structure of dense, narrow stems [25,63]. The main scattering pattern was surface scattering and the intensity was low in August, with the result that the differences in sigma naught were small.…”
Section: Separability Assessmentsmentioning
confidence: 99%
“…However, the quality of optical remote sensing data depends on atmospheric influences and weather conditions. Substantial information about soil and vegetation parameters has been obtained through microwave remote sensing, and this type of technique is increasingly being used to manage land and water resources for agricultural applications [11][12][13][14]. Synthetic aperture radar (SAR) systems offer a large amount of information about soil moisture, crop height, and crop cover rate, which are useful for monitoring plant phenology [12,15].…”
mentioning
confidence: 99%
“…There are examples of uses for crop growth monitoring of beets (Vyas et al 2003), maize (Beriaux et al 2013;Blaes et al 2006), and wheat (Fontanelli et al 2013;Lievens and Verhoest 2011;Mattia et al 2003;Sonobe et al 2014c). Furthermore, SAR data have been used to identify specific crop types, such as paddy fields (Choudhury and Chakraborty 2006;Kuenzer and Knauer 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are primarily crop height, crop LAI and crop biomass. Sonobe et al (2014) measured the height, moisture content and dry matter of the crops during nearly the same interval time as the collection of the TerraSAR-X data in the same area and studied the relationships between the measured parameters and the SAR data, including the sigma naught and coherence. The results confirmed that the X-band SAR data possessed great potential for the development of an operational system for monitoring wheat growth (Sonobe et al 2014).…”
Section: Crop Parameter Estimationmentioning
confidence: 99%